Bitcoin: investimento do século ou bolha especulativa? Mensuração do risco individual do bitcoin sobre o risco sistêmico do mercado de capitais do Brasil e EUA - Simão, Bárbara Correia (2018)
Lately, digital currencies have received meaningful representation in economies around the world, as a result to its agility, security and the low cost associated in the transactions. With the propose of revolution the monetary system, the virtual currency denominated by Bitcoin suggests an electronic payment system with open software based on the cryptography, in which it does not allow banks or any other central entities to intermed the transactions. Bitcoin users give this coin two different roles. First, Bitcoin may act as a means of payment for exchanges goods and services. Second, Bitcoin has been targeted for speculative purposes because of the high volatility of its value in the financial market (HUR, JEON and YOO, 2015). In addition, the operating protocol established by Bitcoin allows transactions between users to remain anonymous. Therefore, the absence of a regulatory institution for digital currency transactions has raised a debate about Bitcoin's contribution to promoting illegal activities. In this context, the present research seeks to obtain inferences about the contribution of Bitcoin's individual risk on the financial system of Brazil and the United States, in order to signal regulatory authorities to a positionally adequate level of financial intermediation. The research methodology consists of the use of the systemic risk estimation models CoVaR, CoVaR GARCH, ?CoVaR and ?CoVaR GARCH. The research results aims to contribute to the provision of macro-prudential information, in order to mark the intervention of financial control institutions around the implementation of regulatory measures for Bitcoin. Overall, the results indicate that Bitcoin's individual risk affects systemic risk and in extreme event scenarios Bitcoin is significant in reducing the systemic risk of the Brazilian and American capital markets.